Accuracy of Neck Circumference in Classifying Overweight and Obese US Children. (30th January 2014) - Kim, Youngwon; Lee, Jung-Min; Laurson, Kelly; Bai, Yang; Gaesser, Glenn A.; Welk, Gregory J.
Abstract : Objective. To evaluate classification accuracy of NC and compare it with body mass index (BMI) in identifying overweight/obese US children. Methods. Data were collected from 92 children (boys: 61) aged 7 to 13 over a 2-year period. NC, BMI, and percent of body fat (BF%) were measured in each child and their corresponding cut-off values were applied to classify the children as being overweight/obese. Classification accuracy of NC and BMI was systematically investigated for boys and girls in relation to true overweight/obesity categorization as assessed with a criterion measure of BF% (i.e., Bod Pod). Results. For boys, Cohen's κ (0.25), sensitivity (38.1%), and specificity (85.0%) of NC were smaller in comparison with Cohen's κ (0.57), sensitivity (57.1%), and specificity (95.0%) of BMI in relation to BF% categorization. For girls, Cohen's κ (0.45), sensitivity (50.0%), and specificity (91.3%) of NC were smaller in comparison with Cohen's κ (0.52), sensitivity (50.0%), and specificity (95.7%) of BMI. Conclusion. NC measurement was not better than BMI in classifying childhood overweight/obesity and, for boys, NC was inferior to BMI. Pediatricians and/or pediatric researchers should be cautious or wary about incorporating NC measurements in their pediatric care and/or research.